The Influence of Marketing Mix on Repurchase Decisions of Training and Certification Services in the Field of Information Technology (Case Study at PT Inixindo Amiete Mandiri Bandung) - Herawati Herawati; Mariana Rachmawati (Dinasti Review, 2026)
This study aims to analyze the influence of the service marketing mix, consisting of product, price, place, promotion, people, physical evidence, and process, on repeat purchase decisions for training and certification services in the field of information technology at PT Inixindo Amiete Mandiri Bandung. The research method used is quantitative with a descriptive and verification approach. Data were collected through questionnaires distributed to 84 respondents who participated in the training and certification program. Data analysis was carried out using multiple linear regression analysis with the help of SPSS software. The results of the study indicate that the service marketing mix simultaneously has a significant influence on repeat purchase decisions. Partially, each component of the service marketing mix also shows a positive and significant influence on repeat purchase decisions. These findings indicate that the implementation of an effective service marketing mix can increase customer interest and loyalty in making repeat purchases. This study is expected to provide valuable insights for the management of PT Inixindo Amiete Mandiri Bandung in developing more effective marketing strategies to increase consumer repeat purchase decisions.